Spectrum averaging in a MIMO FMCW maritime radar for a small fluctuating target range estimation - Abd. Rashid, Nur Emileen; Zainuddin, Suraya; Ibrahim, Idnin Pasya; Raja Abdullah, Raja Syamsul Azmir; Ismail Khan, Zuhani (Taylor's University, 2022)
Detection of a small maritime target has been challenging in radar signal processing due to the object size near the water surface. This paper provides an alternative detection method for a small fluctuating target by deploying a frequency modulated continuous waveform (FMCW) in a multiple-input multiple-output (MIMO) configuration. The work proposed a MIMO FMCW radar with a frequency offset between transmitted sub-bands, and the spectrum averaging (SA) scheme to combine the multiple received signals. A MIMO with an equal number of transmit and receive nodes were employed, and transceivers were co-located. The frequency-offset introduced an interval band between MIMO sub-signals to avoid interference and overlapping. The work observed range error parameters of a small fluctuating target. The result reveals that applying the SA with and without an interval band produced a better performance against signal-to-noise ratio (SNR) in terms of probability of range error and range error mean, through numerical simulations and experiments. However, MIMO caused an incremental computational complexity with the number of nodes based on Fast Fourier Transform (FFT) algorithm